2017
DOI: 10.1021/acssuschemeng.7b00976
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of the Oleaginous YeastRhodosporidium diobovatumto Biodiesel Using the Ionic Liquid [C2mim][EtSO4]

Abstract: In this study, the direct conversion of wet oleaginous yeast biomass to fatty acid methyl esters (FAME) using base transesterification in the presence of an ionic liquid was optimized. The ionic liquid, 1-ethyl-3-methylimidazolium ethylsulfate, was used to facilitate this process and improved the yields of FAME transesterified directly from wet biomass using potassium hydroxide (KOH) as a catalyst. Factorial screening was first used to identify critical factors affecting the transesterification yield, and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, it has been reported that up to 70% of the cost to make biodiesel could be accrued after the production of the cell biomass, when chemical methods of extracting TAGs are used [80]. This is a costly process that requires the complete drying of biomass, full chemical diffusion of solvent into the cells [81], yeast cell wall disruption, and lipid extraction [2].…”
Section: Rhodosporidium Diobovatummentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been reported that up to 70% of the cost to make biodiesel could be accrued after the production of the cell biomass, when chemical methods of extracting TAGs are used [80]. This is a costly process that requires the complete drying of biomass, full chemical diffusion of solvent into the cells [81], yeast cell wall disruption, and lipid extraction [2].…”
Section: Rhodosporidium Diobovatummentioning
confidence: 99%
“…This same method was effective for R. diobovatum and was optimized to produce 97.1% conversion of maximum FAME yields in 2.5 hours at 65°C. They did note a loss of ~40% of their KOH catalyst but conclude that switching from a homogenous to a heterogeneous catalyst could mitigate this [80]. Therefore, research is ongoing to develop R. diobovatum as top biofuel production species.…”
Section: Rhodosporidium Diobovatummentioning
confidence: 99%
“…Ionic liquids (ILs) have been shown to increase the lipid extraction efficiency from microalgae by dissolving both dry and wet microalgae under relatively mild conditions (80–140 °C) with and without a co-solvent ( Table 1 ) [ 1 , 30 , 31 ]. ILs are often described as “green” designer solvents with many desirable physical-chemical properties such as great thermal stability, low melting points, and negligible vapor pressure [ 32 ]. In bioprocessing, ILs are best known for the capability of some ionic liquids to solvate highly recalcitrant biopolymers like cellulose [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The synergetic effect of combining IL – methanol solvent and microwave heating produced biodiesel in 42 % yield based on dry biomass weight . The direct conversion of wet oleaginous yeast biomass to fatty acid biodiesel using 1‐ethyl‐3‐methylimidazoliumethylsulfate and KOH is also known . Some of the more recent (after 2012) applications of ILs in biodiesel synthesis are shown in Table .…”
Section: Biodiesel Synthesis Using Ionic Liquidsmentioning
confidence: 99%